APLIKASI BELAJAR BERHITUNG BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - Game is one of the huge industry on the android phones. Game is a combination of the interactivity of multimedia, games right now has been proven to be something that very interesting in the society. Not only  for children, but also parents play it. Basically games was created just for entertainment but it would be better if games created as a learning tool, because learning is one of the process for us to increase knowledge and insight to be more. Unfortunately the potential of this kind is still rare for the positive purposes one of them are games which is combines the elements of education and entertainment. In this study the writer tried to apply some game for smartphones that can be used for play and learn. This game is talking about calculation sort of addition, subtraction, multiplication, and randomly. Contains questions about random addition, subtraction and multiplication. The writer made an application using Corona and Lua programming language. The result of the development of this system is an arcade games which presents a math game is not only fun and entertaining, but also estabilish the player's ability in arithmetic. Keywords:  Game, Arcade, Math, Education, Corona, LUA.